Enhancing the performance of InGaN/GaN multiple quantum well blue laser diodes by suppressing the overflow of holes. (August 2018) - Yang, J.; Zhao, D.G.; Jiang, D.S.; Chen, P.; Zhu, J.J.; Liu, Z.S.; Liu, W.; Liang, F.; Liu, S.T.; Xing, Y.; Li, M.
Abstract: Transportation of carriers in c-plane InGaN-based blue laser diodes (LDs) has been investigated by both experimental and simulation methods. It is found that excepting the leakage of electrons, holes may overflow from InGaN/GaN multiple quantum wells (MQWs) and enter into InGaN lower waveguide (LWG) layer. It leads to the increase of recombination rate in LWG layer and results in the waste of carriers. Ultimately degrades the performance of LDs. In addition, we also found that reducing the thickness of GaN first barrier (FB) layer can suppress the leakage of holes due to the decrease of the effective depth of potential well in InGaN LWG layer, a lower effective depth of potential well in InGaN LWG layer is helpful the holes coming back to well layer and therefore the threshold current decreases to 80% when the FB layer thickness decreases from 20 nm to 1 nm. Highlights: Transportation of carriers in c-plane InGaN-based blue laser diodes (LDs) has been investigated. Some of holes may overflow from MQWs and recombine in InGaN lower waveguide (LWG) layer in LDs. Removing the GaN FB layer can suppress the leakage of holes in InGaN based blue LDs.